Activation of canonical wnt pathway promotes differentiation of mouse bone marrow‐derived MSCs into type II alveolar epithelial cells, confers resistance to oxidative stress, and promotes their migration to injured lung tissue in vitro. Issue 6 (25th February 2013) - Liu, Ai‐ran; Liu, Le; Chen, Song; Yang, Yi; Zhao, Hong‐jie; Liu, Ling; Guo, Feng‐mei; Lu, Xiao‐min; Qiu, Hai‐bo
Abstract The differentiation of mesenchymal stem cells (MSCs) into type II alveolar epithelial (AT II) cells in vivo and in vitro, is critical for reepithelization and recovery in acute lung injury (ALI), but the mechanisms responsible for differentiation are unclear. In the present study, we investigated the role of the canonical wnt pathway in the differentiation of mouse bone marrow‐derived MSCs (mMSCs) into AT II cells. Using a modified co‐culture system with murine lung epithelial‐12 (MLE‐12) cells and small airway growth media (SAGM) to efficiently drive mMSCs differentiation, we found that GSK 3β and β‐catenin in the canonical wnt pathway were up‐regulated during differentiation. The levels of surfactant protein (SP) C, SPB, and SPD, the specific markers of AT II cells, correspondingly increased in mMSCs when Wnt3a or LiCl was added to the co‐culture system to activate wnt/β‐catenin signaling. The expression of these factors was depressed to some extent by inhibiting the pathway with the addition of DKK 1. The differentiation rate of mMSCs also depends on their abilities to accumulate and survive in inflammatory tissue. Our results suggested that the activation of wnt/β‐catenin signaling promoted mMSCs migration towards ALI mouse‐derived lung tissue in a Transwell assay, and ameliorated the cell death and the reduction of Bcl‐2/Bax induced by H2O2, which simultaneously caused reduced GSK 3β and β‐catenin in mMSCs. These data supports a potential mechanism for the differentiation of mMSCs into AT II cells involving canonical wnt pathway activation, which may be significant to their application in ALI. J. Cell. Physiol. 228: 1270–1283, 2013. © 2012 Wiley Periodicals, Inc.